Advantages and disadvantages of patients’ hospitalization in Intensive Care Units - Kafantaris, Spyridon; Kadda, Olga (Health & Research Journal, 2021)
Background: An Intensive Care Unit (ICU) is a special hospital department with many advantages and disadvantages for the patient. Aim: The aim of the present systematic review was to explore the advantages and disadvantages of hospitalized ICU patients. Material and Method: A literature review in international databases (Pubmed, Cinahl, Google Scholar, Cochrane Library) was conducted. A time limited criteria was applied with respect to the publication of articles (articles published in the last 15 years). Ten articles were found that met the criteria for participation in the present review. Results: Results thematic analysis revealed the following advantages and disadvantages of ICU hospitalization: Advantages related to patients care in ICU and advantages related to team work. Disadvantages related to the ICU environment (noise, lighting) that complicate the patient’s hospitalization status and cause the patient’s sleep disturbances and / or delirium. Additionally, it was found that financial cost of hospitalization is a very significant disadvantage for both patient and health care providers. Conclusions: Preparation and successful implementation of significant strategies will convert disadvantages of ICU hospitalization into advantages in daily clinical practice through increased use of protocols, the maintenance of a checklist, evidenced based practice, data recording, development of interdisciplinary groups and finally the extensive application of technology for patient’ s benefit.